(untitled) (Journal of Event, Tourism and Hospitality Studies, 2024)
Sports play a significant place in Malaysian culture, serving as both a spectator and participant activity. Organized badminton events have the potential to enhance sport tourism revenue by drawing in both local and international fans keen to support their favourite teams. Understanding the motivations of specific market segments, particularly the youth, is vital for effective sports industry marketing. However, a lack of motivation among youth to attend badminton events can lead to diminished interest in these events. Consequently, this study aims to examine the factors influencing the motivation of youth to attend badminton matches in Malaysia. The study’s sample comprises 341 students from UUM, selected through convenience sampling technique. The findings reveal that self-esteem is the foremost motivation for attending badminton matches (mean=4.31), followed by factors of group (mean=4.30), family (mean=4.17), entertainment (mean=4.08), escape (mean=3.98), eustress (mean=3.94), and aesthetics (mean=3.37). Furthermore, most respondents identify as badminton fans, indicating potential growth opportunities for the badminton industry. Understanding fan motivations can enable the industry to better meet their needs, thereby contributing to its expansion and success. This study underscores the importance of engaging youth in badminton events to foster sustained interest and participation in sports tourism initiatives.